2019
DOI: 10.3390/cancers11040544
|View full text |Cite
|
Sign up to set email alerts
|

CHI3L1, NTRK2, 1p/19q and IDH Status Predicts Prognosis in Glioma

Abstract: The aim of this study was to identify relevant biomarkers for the prognosis of glioma considering current molecular changes such as IDH mutation and 1p19q deletion. Gene expression profiling was performed using the TaqMan Low Density Array and hierarchical clustering using 96 selected genes in 64 patients with newly diagnosed glioma. The expression dataset was validated on a large independent cohort from The Cancer Genome Atlas (TCGA) database. A differential expression panel of 26 genes discriminated two prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 52 publications
2
12
0
Order By: Relevance
“…27 To improve prognosis prediction, other genes associated with IDH and 1p19q status need to be identified. 18,28 In this study, we revealed that PLOD1 expression was higher in glioma patients with IDH wildtype and 1p19q codeletion. Furthermore, PLOD1 was a supplementary prognostic marker for IDH1 and 1p19q status in predicting the outcome of glioma patients.…”
mentioning
confidence: 59%
“…27 To improve prognosis prediction, other genes associated with IDH and 1p19q status need to be identified. 18,28 In this study, we revealed that PLOD1 expression was higher in glioma patients with IDH wildtype and 1p19q codeletion. Furthermore, PLOD1 was a supplementary prognostic marker for IDH1 and 1p19q status in predicting the outcome of glioma patients.…”
mentioning
confidence: 59%
“…The OSMR (receptor for the cytokine Oncostatin M) is a regulator of brain tumor stem cells (BTSC) proliferation by mediating EGFR phosphorylation [ 40 ]. CHI3L1 can be associated with IDH status and 1p/19q co-deletion in patients with glioma [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…NTRK1 promoted proliferation and metastasis of cancer cells and lead to poor prognosis in multiple cancers (13)(14)(15)(16)(17), while it suppressed cell proliferation in neuroblastoma (18). NTRK2 was shown to serve as an oncogene in multiple cancers (19)(20)(21)(22), and its increased expression was associated with poor outcome (23,24). Based on this, inhibition of NTRK2-encoded TRKB was shown to induce antitumor effects and cellular apoptosis (25,26).…”
Section: Introductionmentioning
confidence: 99%